Peningkatan Profesionalisme Guru SMKN 2 Semarang Melalui Pengembangan Manajemen Waktu Berbasis Digital - Hengky Pramusinto; Agung Kuswantoro; Wisudani Rahmaningtyas; Alvi Mukhifudin; Zakkya Mar’a S; Chandra Alifian Syah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Community service activities carried out by the Community Service Team for teachers at SMKN 2 Semarang City aim to provide knowledge and skills regarding increasing teacher professionalism through the development of digital-based time management, namely Google Calendar. The direct benefit of this community service activity is that it provides additional knowledge, skills and experience for SMKN 2 Semarang teachers in increasing their professionalism in performance through well-designed time management. The expected derivative benefit is an increase in teachers' ability to develop themselves because planning, organizing and implementing activities based on performance targets will be able to improve the quality of work and ultimately will be able to increase the professionalism of the teachers themselves. This community service activity is carried out in the form of training by providing material and practices for developing digital-based time management via the Google Calendar platform. The target audience for this community service activity is representatives of teachers at SMKN 2 Semarang and 20 teachers who are members of the MGMP MPLB Semarang City. The activity methods used in this community service are lecture, question and answer, discussion and practice methods. Evaluation of activities used in community service is the knowledge and skills aspect. The service activity ran smoothly and all participants felt satisfied and happy with this activity because it increased their knowledge and skills in digital-based time management.